2011
DOI: 10.1063/1.3626847
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of conservative and dissipative interactions in bimodal atomic force microscopy using open-loop and phase-locked-loop control of the higher eigenmode

Abstract: We compare the ability of higher cantilever eigenmodes to map conservative and dissipative tip-sample interactions in bimodal atomic force microscopy under three different control schemes, namely, open-loop (OL), constant-excitation phase-locked-loop (CE-PLL), and constant-amplitude phase-locked-loop (CA-PLL). We perform a direct comparison of these schemes by applying analytical expressions of the virial and dissipated power to imaging and spectroscopy experiments conducted on a two-component polymer sample i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 26 publications
0
74
0
Order By: Relevance
“…[11][12][13] It was shown that the small oscillation of the second flexural mode could be used to increase sensitivity to material properties. [14][15][16][17] Several groups have applied this technique to biological samples, including antibodies 13 and proteins. 11 Schwenk and coworkers used bimodal AFM to increase the contrast stemming from magnetic interaction with a ferromagnetic tip.…”
mentioning
confidence: 99%
“…[11][12][13] It was shown that the small oscillation of the second flexural mode could be used to increase sensitivity to material properties. [14][15][16][17] Several groups have applied this technique to biological samples, including antibodies 13 and proteins. 11 Schwenk and coworkers used bimodal AFM to increase the contrast stemming from magnetic interaction with a ferromagnetic tip.…”
mentioning
confidence: 99%
“…In such cases, as long as the oscillation is not chaotic, the user will generally be able to obtain an image, but imaging stability does not guarantee that the results are physically meaningful, since it does not guarantee that the contrast eigenmodes conform to the assumed ideal response. In contrast, if frequency modulation methods are used to drive the higher modes [5,7,27], it is necessary that the frequency response be well behaved both to ensure the stability of the controls scheme and to guarantee physically meaningful results. Our simulations show that the highest (least perturbable) eigenmodes retain their ideal response even in multimodal operation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the difficulties become even more significant if one wishes to implement bimodal operations involving frequency modulation (FM) control of the higher eigenmode [4]. While the phase contrast results may become less and less meaningful as momentary perturbations become more and more severe, one is still generally able to obtain an image with open loop drive of the higher mode.…”
Section: Resultsmentioning
confidence: 99%